172k views
3 votes
3x+4=6x-9 solve this and show the steps

2 Answers

4 votes

Solving Linear Equations

Answer:


x = (13)/(3)\\

Explanation:


3x +4 = 6x - 9 \\ 3x +4 -6x = 6x -9 -6x \\ -3x +4 = -9 \\ -3x +4 -4 = -9 -4 \\ -3x = -13 \\ (-3x)/(-3) = (-13)/(-3) \\ x = (13)/(3)

User Anaxin
by
5.3k points
4 votes

Answer:

Explanation:

3x+4-4=6x-9-4 subtract 4 from both sides

3x = 6x - 13 Simplify

3x-6x = 6x - 13 - 6x

-3x = - 13

-3x/-3 = -13/-3

x = 13/3

I hope this helps. Please let me know if it's useful.

User Iammichael
by
6.2k points